Self‐Construction from 2D to 3D: One‐Pot Layer‐by‐Layer Assembly of Graphene Oxide Sheets Held Together by Coordination Polymers. Issue 29 (11th May 2016) - Zakaria, Mohamed B.; Li, Cuiling; Ji, Qingmin; Jiang, Bo; Tominaka, Satoshi; Ide, Yusuke; Hill, Jonathan P.; Ariga, Katsuhiko; Yamauchi, Yusuke
Abstract: Deposition of Ni‐based cyanide bridged coordination polymer (NiCNNi) flakes onto the surfaces of graphene oxide (GO) sheets, which allows precise control of the resulting lamellar nanoarchitecture by in situ crystallization, is reported. GO sheets are utilized as nucleation sites that promote the optimized crystal growth of NiCNNi flakes. The NiCNNi‐coated GO sheets then self‐assemble and are stabilized as ordered lamellar nanomaterials. Regulated thermal treatment under nitrogen results in a Ni3 C–GO composite with a similar morphology to the starting material, and the Ni3 C–GO composite exhibits outstanding electrocatalytic activity and excellent durability for the oxygen reduction reaction. Abstract : Layer cake : Deposition of nickel‐based cyano‐bridged coordination polymer (NiCNNi) flakes on the surface of graphene oxide (GO) sheets allows the formation of lamellar nanoarchitectures. Regulated thermal treatment under nitrogen produces an Ni3 C–GO composite with a similar morphology to the starting material. This approach may be applicable to other inorganic–organic hybrids for the formation of ordered layer‐by‐layer (LbL) architectures.